Effect of hyperoxia on articular tissues in organ culture. - Jubb, R W (1979)
The effect of hyperoxia on pig articular tissue has been studied in organ culture. Hyperoxia (55% O2) causes an increased release of hydroxyproline and collagenolytic activity from synovial tissue as compared with control explants in 20% O2, but neither 55% nor 95% O2 has any effect on the breakdown of isolated cartilage during 10 days in culture. When synovium and cartilage are cultured in contact, the breakdown of cartilage collagen is greater in the hyperoxic (55% O2) group than in the controls (20% O2), but the breakdown of proteoglycan is not increased. The enhanced collagenolytic action is due to an increase in the direct effect of the synovial tissue on the cartilage matrix. In 20% O2 the synovium causes the chondrocytes to degrade the cartilage matrix, but this effect is inhibited by 55% O2.